A GIS-BASED TSUNAMI EVACUATION MODEL CONSIDERING LAND COVER AND SPATIAL CONFIGURATION (CASE OF PURWOREJO REGENCY, INDONESIA) - Febri Fahmi Hakim; Walter Timo de Vries; Florian Siegert; Joesron Alie Syahbana (Department of Urban and Regional Planning, Diponegoro University, 2017)
In Indonesia, several programs have dealt with tsunami mitigation, such as The German-Indonesian Tsunami Early Warning System (GITEWS) project (2005-2011). Despite the success of these projects, many coastal areas in Indonesia are still vulnerable to tsunamis, due to the variety of land cover and spatial configuration characteristics. One of such vulnerable areas includes Purworejo Regency. This paper evaluated the degree to which land cover and spatial configuration characteristics influence the tsunami evacuation process, and thus influence tsunami hazard mitigation. The evaluation drawn on data from a low to medium density populated coastal area of Purworejo Regency. The analysis relied on a quantitative approach, using a cross-sectional field survey, followed by a GIS-based analysis. This is complemented by a raster-based analysis to incorporate the land cover and spatial configuration aspects. The combined analysis derived which buildings could act as evacuation buildings in case of a tsunami. The associated tsunami evacuation routes were calculated using a Least Cost Path (LCP) analysis method. The results suggested that several public facility buildings are likely to be used as tsunami evacuation buildings. Yet, even though the overall capacity of these buildings is adequate to accommodate the estimated number of evacuees in a larger area, the specific demand at certain locations in the study area is much higher than these localities can handle. This disproportionate spatial variation in required capacity needs further attention. Moreover, the survey responses indicated that the majority of the respondents was not well informed regarding the tsunami evacuation procedures